Antenatal Care Practices in Rangeli VDC of Morang District, Nepal - Sah, RB; Subedi, L; Shah, U; Jha, N; Pokharel, PK (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Nepal has one of the worst maternal and perinatal morbidity and mortality due to the lack of antenatal care (ANC) practices of pregnant women.The objective of this study was to find out the ANC practices and to find out the association between sociodemographic characteristics and antenatal care visits. MATERIAL AND METHODS: The cross-sectional study was conducted from 1st March to 14th March, 2014 among the residents of Rangeli VDC of Morang District in Eastern Nepal where 300 households were taken as subjects. Simple random sampling technique was applied for data collection. Semi-structured questionnaire was used and face to face interview was conducted. Chi-square test was applied to find out the association between sociodemographic characteristics and antenatal care visits.RESULTS: Almost fifty five percent of respondents attended ANC visits.The findings revealed that about 55% received iron, calcium and folic acid tablets and almost 61% of the pregnant women took the tetanus toxoid (TT) injections among who attended ANC. Almost 54.6% of pregnant Hindu women have completed four ANC visits. Women with School Leaving Certificate (SLC) and higher education level was more likely to ANC visits (100%) than women with below SLC (73%) and no education (25%). Furthermore, education of husband shows stronger association with ANC visits (P